ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI BERDASARKAN SISTEM ACTIVITY BASED COSTING PADA PT.FASTFOOD INDONESIA CABANG KFC PLAJU PALEMBANG - Muhammad Umri; Rizal Effendi (JURNAL KOMPETITIF, 2018)
The accuracy of determination of cost of goods sold is influenced by the accuracy in the accumulation and calculation of production costs which include the cost of raw materials, direct labor costs and other factory costs (factory overhead costs).Cost of production or product cost is an important element to assess the success (performance) of trading companies and manufacturers. The cost of production is closely related to the indicators of corporate success, such as: gross sales, net income. Depending on the ratio between the selling price and the cost of the product, a change in the cost of the product is relatively small so it has a significant impact on the success indicator. Keywords: Cost of Goods Sold, Performance